2020
DOI: 10.1080/13102818.2020.1788421
|View full text |Cite
|
Sign up to set email alerts
|

Morphological alterations in gram-positive and gram-negative bacteria exposed to minimal inhibitory and bactericidal concentration of raw Malaysian stingless bee honey

Abstract: The stingless bee Heterotrigona itama honey is generating interest among consumers due to unique antibacterial properties. Despite the substantial health benefits of this honey, its action mode of inhibiting and killing pathogenic bacteria remains unresolved. The present study aimed to unravel the effect of raw H. itama honey against four clinically important bacteria, Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis and Staphylococcus aureus. Total phenolic and total flavonoid contents, alongside a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…Electron microscopic observation indicated that E. coli cells treated with diluted Shaoka honey showed distorted cell morphologies, including shrinkage in cells, and related to cell permeability change, there was evidence of decrease and leakage of intracellular content and cell-wall destruction, which lead to cell death. Similar results have been shown in the mechanisms of actions of phenolic compounds, which caused cell death by the loss of cellular membrane integrity of function ( Yaacob et al, 2020 ). Other researchers have also reported that the antibacterial mechanisms of flavonoids are assumed to have effects including inhibition of nucleic acid synthesis, alteration of cytoplasmic membrane and function, alteration of membrane permeability, and attenuation of pathogenicity ( Xie et al, 2015 , Jibril et al, 2019 ).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Electron microscopic observation indicated that E. coli cells treated with diluted Shaoka honey showed distorted cell morphologies, including shrinkage in cells, and related to cell permeability change, there was evidence of decrease and leakage of intracellular content and cell-wall destruction, which lead to cell death. Similar results have been shown in the mechanisms of actions of phenolic compounds, which caused cell death by the loss of cellular membrane integrity of function ( Yaacob et al, 2020 ). Other researchers have also reported that the antibacterial mechanisms of flavonoids are assumed to have effects including inhibition of nucleic acid synthesis, alteration of cytoplasmic membrane and function, alteration of membrane permeability, and attenuation of pathogenicity ( Xie et al, 2015 , Jibril et al, 2019 ).…”
Section: Discussionsupporting
confidence: 82%
“…It is scientifically proven to prevent and treat many diseases, such as cancers, microbial infections, oxidative stress, diabetes, burns and wounds, infertility, high blood pressure, and immunodeficiency ( Oryan et al, 2016 , Eteraf-Oskouei and Najafi, 2013 ). It has been established as a bactericidal drug with broad-spectrum activity against Gram-positive and Gram-negative bacterial species ( Yaacob et al, 2020 , Almasaudi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a study of Heterotrigona itama honey by Nuratiqah et al [8] with a total of four honey samples in which each sample was collected from different parts of Peninsular Malaysia showed different values of TPC, ranging from 52.71 to 80.71 mg GAE/100 g. The author mentioned that the different values of TPC were not only influenced by geographical and botanical factors but also together with the selective floral behaviour and the longer and earlier foraging time of the bees. On the other hand, Ismail et al [39] reported in their study that Apini and Meliponini foraging activities influence the phenolic content of different types of Malaysian honey, and the TPC values of stingless bee honey were reported to be lower than European honeybee honey.…”
Section: Total Phenolic Contentmentioning
confidence: 99%
“…It has been proven that stingless bee honey has the potential to inhibit bacteria [8,18,25,30,[53][54][55][56][57][58]. Researchers Hasali et al [58] stated that honey produced by Heterotrigona itama showed greater inhibition of P. aeruginosa compared to commercial antibiotics, indicating better antibacterial activity against pathogenic bacteria.…”
Section: Antimicrobialmentioning
confidence: 99%
See 1 more Smart Citation